Super-shoes: Do male triathletes reap the benefits? - Keats, S. (Auckland University of Technology, 2023)
Background: Running performance is the greatest contributor to overall race time in long-distance triathlon. Therefore, triathletes are constantly on the search for strategies to enhance their running performance, and recent advances in running footwear (`super shoes`) appear to offer a potential solution. There is evidence from studies of runners to support a positive impact of super shoes on performance, but there is no evidence to suggest that these improvements necessarily carry over to long-distance triathletes, where their effect could be moderated by the preceding cycle. Additionally, much of the running-related evidence is related to elite-level athletes, and there is a need to examine the effects of super shoes in age-group (non-elite) athletes.